TMEM231 Gene Conversion Associated with Joubert and Meckel–Gruber Syndromes in the Same Family. Issue 11 (21st August 2016) - Maglic, Dino; Stephen, Joshi; Malicdan, May Christine V.; Guo, Jennifer; Fischer, Roxanne; Konzman, Daniel; ,; Mullikin, James C.; Gahl, William A.; Vilboux, Thierry; Gunay‐Aygun, Meral
Abstract : In a family with Joubert and Meckel‐Gruber Syndromes, we identified a new pathologic variant in TMEM231. This variant is the results of a gene conversion that occurred between TMEM231 and its paralog, LOC100420067, located 40kb downstream the gene. This gene conversion induces 23 differences at the nucleotide level including a splicing variant that leads to the loss of exon 4 at the transcript level. Our report adds TMEM231 to the growing list of genes prone to gene conversion. ABSTRACT: Joubert and Meckel–Gruber syndromes (JS and MGS) are ciliopathies with overlapping features. JS patients manifest the "molar tooth sign" on brain imaging and variable eye, kidney, and liver disease. MGS presents with polycystic kidneys, occipital encephalocele, and polydactyly; it is typically perinatally fatal. Both syndromes are genetically heterogeneous; some genes cause either syndrome. Here, we report two brothers married to unrelated women. The first brother had three daughters with JS and a son with polycystic kidneys who died at birth. The second brother's wife had a fetal demise due to MGS. Whole exome sequencing identified TMEM231 NM_001077416.2: c.784G>A; p.(Asp262Asn) in all children and the wife of the first brother; the second brother's wife had a c.406T>G;p.(Trp136Gly) change. In‐depth analysis uncovered a rare gene conversion event in TMEM231, leading to loss of exon 4, in all the affected children of first brother. We believe that the combination of this gene conversion with different missense mutations led to a spectrum of phenotypes that span JS and MGS.